Analisis Tingkat Pengetahuan Faktor Risiko DM Dengan Status DM Pada Guru SMA Negeri DiKelurahan Paccerakang - Husnul Khatimah (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
The era of globalization has had an impact on all fields, especially in the epidemiological transition of communicable diseases, which gradually decreased, followed by an increase in non-communicable diseases. Diabetes mellitus is the third cause of death in Indonesia after stroke and coronary heart disease. The low level of knowledge is one of the problems in managing diabetes. The purpose of this study was to gain knowledge of DM risk factors with DM status among teachers at SMA Negeri in Paccerakang Village. The research method is descriptive quantitative with a total population of 50 people. The sample involved in this study was 50 people with a total sampling technique. The study was conducted for 1 month and data was collected using a questionnaire with univariate analysis. The results of the research are categorized into good, enough and less. The results showed that there were 78% of respondents who had good knowledge and then enough respondents with less knowledge level of 22%. Based on the results of the test analysis in bivariate analysis, it shows p value = 0.125 (> 0.05) so that there is no relationship between the level of knowledge of DM risk factors and DM status among public high school teachers in Paccerakang Village in 2022. It is recommended that schools make an educational program to increase knowledge public high school teachers in the Paccerakang sub-district who can work with health facilities in the Paccerakang sub-district.